Carbon use efficiency of alpine grasslands affected by grazing exclusion and local environmental context in Tibet, China - Yunfei Feng; Jianshuang Wu; Meng Li; Ben Chen; Minyahel Tilahun; Xianzhou Zhang (Global Ecology and Conservation)
Carbon use efficiency (CUE) is essential for understanding how climate change impacts carbon fixation by vegetation across diverse ecosystems globally. However, the effects of anthropogenic efforts, such as ecosystem restoration of degraded grasslands via livestock grazing exclusion with fences on the spatiotemporal variation in CUE under ongoing climate change remain poorly evaluated and understood. In this study, we calculated CUE values for fenced and adjacent grazed alpine grasslands in Tibet, China. We considered soil properties, topographical features, and climate conditions as potential predictors to explain the spatial patterns and temporal dynamics of CUE across these grasslands. Our results showed that the annual mean CUE of fenced vs. grazed grasslands were similar with values of 0.6961 and 0.6956 across the whole plateau. However, the annual CUE of fenced grasslands increased at a faster rate (6.89 × 10−5 per year) compared to grazed grasslands (0.23 × 10−5 per year) from 2006 to 2019. CUE also exhibited substantial variation across alpine grassland communities, with the highest values observed in alpine steppe meadows under both fenced and grazed management. Precipitation was identified as the most influential factor controlling the spatial pattern of CUE and showed a significant negative correlation with CUE. Moreover, the presence of fences was found to reduce the sensitivity of CUE to in response to varying precipitation. The effectiveness of fences in enhancing CUE primarily depends on local environmental conditions. Our study sheds light on the interplays between ecological restoration efforts and climate change in shaping the CUE dynamics of alpine grasslands on the Tibetan Plateau and emphasizes the importance of local environmental contexts when programming and implementing restoration projects.